Evaluation of Muscle Activities on Different Type of Exercises During Prolonged Sitting - Salim, Mohammad Shahril; Mohd Nawi, Nor Fatihah Fujrah; Salleh, Ahmad Faizal; Omar, Nurhidayah; Awang, Saidatul Ardeenawatie (Emerging Advances in Integrated Technology, 2021)
Abstract: Electromyography (EMG) signal is an analysis of electrical signals generated during muscular contractions that have been used to measure and record electrical muscle activity usually applied for medical tests. In this research EMG signal is used to; (1) evaluate muscle activations on different gender during prolonged sitting task; (2) investigate the influence of various types of exercise during prolonged sitting on muscle activation and (3) proposed the best exercise that can help to prevent low back discomfort. Twenty subjects (10 males and 10 females) were recruited from undergraduate engineering studentâ€™s education background in UniMAP with age ranging between 20 to 24 years old. The subject must be asymptomatic back pain, normal BMI and right-handed. . Three different types of sitting, one hour per sitting were done by each subject in order to reach the goals of this study. First sitting (sitting without exercise) was conducted while second and third sitting (sitting with exercise) were done in order the investigate the effectiveness of the exercises. Two different types of exercise were performed in second and third sitting, both of exercises were chosen from Mc Kenzieâ€™s exercise. EEGOTM sport device were used to record the EMG signal from four types of muscles which are Erector Spinae, Latissimus Dorsi, Internal Oblique and External Oblique. By comparing the Root Mean Square (RMS) values from EMG signals muscle activation during prolonged sitting and the effectiveness of performing the exercises have been evaluated based on RMS values. As the results, muscle become deactivate during prolonged sitting. The best exercise to reduce back pain discomfort is exercise type 1 (Seated Lumbar Exercise) and it is recommended to perform this exercise regularly to reduce the risk of getting hazardous disease due to prolonged sitting. Keywords: Prolonged sitting, muscle activity, exercises on prolonged sitting